The Impact of the First Covid 19 Pandemic on Urology Residency Training in Iran - Abedi, Amir Reza; Aliakbari, Fereshteh; Ghiasy, Saleh; Allameh, Farzad; Ghanbari, Mohammad Ali (Archives of Men's Health, 2020)
Background: During the pandemic, Iranian healthcare system had faced many challenges including the continuation of medical education. In this time, almost all elective surgeries have been suspended, outpatient visits have been limited to seriously ill patients, and academic meeting have been cancelled. This process has caused a significant decrease in clinical and surgical practice in the field of urology. In this article, we assess as to what extent and how this pandemic has impacted the urology residency training in Iran. Material and Methods: a 15-item-long questionnaire was designed and sent to all Iranian urology residents via social network and/or email from the 10th of MAY to the 10th of Jun 2020. This questionnaire assessed different training activities, including on-call duty, outpatient visits, diagnostic procedures such as cystoscopy, endoscopic procedures, and open major surgeries, prior and during the pandemic. The results were evaluated using t-test and ANOVA. Results: the percentage of urology resident’s involvement in each training activity, including on-call duty, outpatient visits, diagnostic procedures such as cystoscopy, endoscopic procedures, and open major surgeries, demonstrated a significant decline (p<0.001) during this time compared to the pre-COVID-19 period. Conclusion: urology residency training significantly decreased during the COVID-19 period. In order to address the second and third waves of COVID-19 outbreak, long-term action plans, such as telemedicine and stimulation, can help prepare training programs and residents during these unprecedented times.